Clinical and endoscopic features of pill-induced esophagitis - Patel, Dhruv Kumar M.; Panchal, Yash N.; Patel, Maitri M.; Rajput, Sanjay L.; Patel, Mukundkumar V.; Patel, Mayank J. (International Journal of Basic & Clinical Pharmacology, 2022)
Background: Medication can cause an injury in the esophagus by local and systemic effect, leading to esophagitis. Many such medications have been identified as a cause of pill-induced esophagitis. This study was performed to evaluate the clinical and endoscopic findings of pill-induced esophagitis. Methods: This was retrospective observational study, conducted among patients diagnosed endoscopically with pill-induced esophagitis at Ansh gastroenterology clinic, Ahmedabad, India, from April 2017 to March 2021. The data of these patients were recorded in pre-designed case record form by evaluating their past medical records. Results: Total 90 patients were diagnosed with pill-induced esophagitis. Retrosternal chest pain (68.9%), odynophagia (41.1%), dysphagia (25.6%), and epigastric pain (14.4%) were common clinical findings. The major culprit medications were antibiotics, and NSAIDs (non-steroidal anti-inflammatory drugs). Common esophageal endoscopic findings were ulcer (84.4%), erosion (17.8%), and active ulcer bleeding (12.2%). Kissing ulcers were observed in the majority (46.7%) of cases. The majority of ulcer and erosion were located in middle third of the esophagus. All the patients were recovered within 6 to 10 days after treatment with PPIs (proton pump inhibitors) and/or antacids, and withdrawal of the causative medication. Conclusions: Pill-induced esophagitis commonly manifests as retrosternal chest pain, odynophagia and dysphagia, and endoscopy reveals kissing ulcer and erosion in the majority of cases. The condition can be treated with PPIs and/or antacids, and withdrawal of the offending medication.